Highly multiplexed AmpliSeq technology identifies novel variation of flowering time-related genes in soybean (Glycine max). (16th April 2019) - Ogiso-Tanaka, Eri; Shimizu, Takehiko; Hajika, Makita; Kaga, Akito; Ishimoto, Masao
Abstract: Whole-genome re-sequencing is a powerful approach to detect gene variants, but it is expensive to analyse only the target genes. To circumvent this problem, we attempted to detect novel variants of flowering time-related genes and their homologues in soybean mini-core collection by target re-sequencing using AmpliSeq technology. The average depth of 382 amplicons targeting 29 genes was 1, 237 with 99.85% of the sequence data mapped to the reference genome. Totally, 461 variants were detected, of which 150 sites were novel and not registered in dbSNP. Known and novel variants were detected in the classical maturity loci— E1, E2, E3, and E4 . Additionally, large indel alleles, E1-nl and E3-tr, were successfully identified. Novel loss-of-function and missense variants were found in FT2a, MADS-box, WDR61, phytochromes, and two-component response regulators . The multiple regression analysis showed that four genes —E2, E3, Dt1, and two-component response regulator —can explain 51.1–52.3% of the variation in flowering time of the mini-core collection. Among them, the two-component response regulator with a premature stop codon is a novel gene that has not been reported as a soybean flowering time-related gene. These data suggest that the AmpliSeq technology is a powerful tool to identify novel alleles.